Empirical evaluation of a theory of stigma in children and adolescents with sickle cell disease - Ani, Cornelius; Garralda, Elena; Anie, Kofi A.; Wilkey, Olu; Hodes, Matthew (Advances in Social Sciences Research Journal, 2015)
Background. There is limited research in self-perceived stigma among children and adolescents with sickle cell disease (SCD). We applied the concept of “stigma dimensions” to measure the predictors of self-perceived stigma in young people with SCD. Objective. In accordance with “stigma dimensions”, we hypothesized that young people with visible clinical features of SCD (jaundice and leg ulcers), and greater interference with their daily lives and social activities (frequent hospital admissions and school absences) would have increased self-perceived stigma. Patients and methods. 93 children and adolescents with SCD aged 10-19 years in the UK completed questionnaires on self-perceived stigma. Socio-demographic and clinical characteristics of SCD were also obtained. Young people were recruited from paediatric haematology or sickle cell outpatient clinics in London and the Sickle Cell Society (National Charity). Participants with all types of SCD were included; exclusions were those who were not fluent in English or unwell at the time of the survey. Results. Mean age was 14.2 years (SD 2.1 years) with 51% males and 49% females. 66% of the respondents had one or more hospital admissions in the preceding year, 46% were jaundiced, and 5% had leg ulcers. Consistent with our hypothesis and “stigma dimensions”, regression analysis showed that those who experienced more disruption in their daily lives (frequent hospital admission and less school attendance) had increased self-perceived stigma. However, the presence of leg ulcers or jaundice was not associated with increased self-perceived stigma. Conclusion. Interventions in SCD that effectively moderate disruption of daily activities and improve quality of life could help reduce self-perceived stigma among young people with SCD.